The prohibition of maysir and gharar in the financial contract and contemporary competitions / Nur Anis Syafiqah Malek - Malek, Nur Anis Syafiqah (2019)
As we know, maysir and gharar are forbidden to practice and its prohibition has stated in Quran and Sunnah. Nowadays, the society is involved with the maysir and gharar in their life without their consent or intention. However, regarding the development of technology and life nowadays has create some activities that might be a maysir or gharar and because of that it has create the confusion among society. Hence, there are many questions asked to the authorities towards the evolution’s issues of maysir and gharar that arise. This study is about the application of maysir and gharar in daily life among Muslims society which nowadays, there are elements of maysir and gharar that have been include in many things such as in finance institutions and games. The purpose of this research is to provide the deep understanding about maysir and gharar to the community. This study has provided the concept of maysir and gharar and its issues of applications that involved in society life. The method used is the qualitative method which is library research an online research that its sources is comes from books, journals, articles and authority websites. Hope this research will help the society to get more understanding about maysir and gharar on its application use in their daily life.